Development of the Blangkon Industry in Potrojayan Village 1995-2019 - -, Khunafa Amila Sholihah; Ira Indria Kusuma Ratih; Anida Farisa Rahmawati; Laela Ayu Mutmainah; Hieronymus Purwanta (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
The Blangkon industry produced in the Potrojayan Village area has been running since 1995. This research aims to examine the development of the Blangkon industry from 1995-2019 in Potrojayan Village in terms of the development of craftsmen, production houses and market demand related to blangkon. Data analysis used a qualitative descriptive approach. Data collection was carried out by means of observation, interviews and literature review. This research is located in Pottojayan Village with a period from February to July 2023. The informants in this research are Mr. Ananta Karyana, Mr. Djazuli, Mrs. Munasih, Mr. Latif, Mr. Agung, Mr. Aris, Mrs. Rus, Mr. Arif. The research results show that the blangkon industry in Potrojayan.